Karakter Agronomis dan Fisiologis Tanaman Kopi Robusta (Coffea canephora) pada Dataran Tinggi di Kecamatan Pejawaran Kab. Banjarnegara - Duando Rizki; Bambang Rudianto Wijonarko; Purwanto Purwanto (University of Insan Cendekia Mandiri, 2020)
The agronomic characteristics of Robusta coffee plants are influenced by several factors, one of which is altitude. Robusta coffee can grow optimally at an altitude of 400-1,000 meters above sea level with a temperature of 21-24 °C. Pejawaran sub-district is known as a mountainous area with a height of 900-1600 m above sea level. This research was conducted in July to September 2019 in the coffee garden of Sarwodadi Village, Pejawaran District, Banjarnegara Regency. The selection of research sites was carried out by conducting a survey where 3 altitudes were selected that had a greater number of coffee plants. The research sites include 1,100 m asl, 1,200 m asl and 1,350 m asl, plant samples taken are 10% of the total plant population. Variables observed included chlorophyll a, chlorophyll b, stomata opening, stomata density, plant height, stem diameter, number of productive branches, number of bunches per plant and yield per plant. The results showed that the altitude of 1,100 m asl has chlorophyll content, the number of bunches per plant and yield per plant is better than the other heights of 20.95 mg / g, 8.64 mg / g, 113 and 6.64 kg. The chlorophyll content of a and b is positively related to the number of bunches. Stomatal openings are significantly positive for the number of productive branches. Plant height was negatively related to productive branches and number of bunches. Stem diameter is positively related to the number of bunches. The number of productive branches is positively related to the results.